In vivo label‐free functional photoacoustic monitoring of ischemic reperfusion. Issue 7 (1st April 2019) - Bi, Renzhe; Dinish, U.S.; Goh, Chi Ching; Imai, Toru; Moothanchery, Mohesh; Li, Xiuting; Kim, Jin Young; Jeon, Seungwan; Pu, Yang; Kim, Chulhong; Ng, Lai Guan; Wang, Lihong V.; et al.
Abstract : Pressure ulcer formation is a common problem among patients confined to bed or restricted to wheelchairs. The ulcer forms when the affected skin and underlying tissues go through repeated cycles of ischemia and reperfusion, leading to inflammation. This theory is evident by intravital imaging studies performed in immune cell–specific, fluorescent reporter mouse skin with induced ischemia‐reperfusion (I‐R) injuries. However, traditional confocal or multiphoton microscopy cannot accurately monitor the progression of vascular reperfusion by contrast agents, which leaks into the interstitium under inflammatory conditions. Here, we develop a dual‐wavelength micro electro mechanical system (MEMS) scanning–based optical resolution photoacoustic microscopy (OR‐PAM) system for continuous label‐free functional imaging of vascular reperfusion in an IR mouse model. This MEMS‐OR‐PAM system provides fast scanning speed for concurrent dual‐wavelength imaging, which enables continuous monitoring of the reperfusion process. During reperfusion, the revascularization of blood vessels and the oxygen saturation (sO2 ) changes in both arteries and veins are recorded, from which the local oxygen extraction ratios of the ischemic tissue and the unaffected tissue can be quantified. Our MEMS‐OR‐PAM system provides novel perspectives to understand the I‐R injuries. It solves the problem of dynamic label‐free functional monitoring of the vascular reperfusion at high spatial resolution. Abstract : Illustration of the vascular reperfusion of the ear skin: How does the ischemic tissue revascularize? Now, we can visualize the reperfusion process at high spatial resolution (~ 5 μm) by using a dual‐wavelength micro electro mechanical system scanning–based optical resolution photoacoustic microscopy system. The fast imaging capability enables continuous monitoring of skin reperfusion in a mouse model. It is also found that the ischemic tissue has a significantly higher oxygen consumption rate in the reperfusion stage comparing to the normal tissue.